Elampus foveatus - Paukkunen, Juho; Rosa, Paolo; Soon, Villu; Johansson, Niklas; Ødegaard, Frode (Zenodo, 2014)
13. Elampus foveatus (Mocsáry, 1914) Ellampus foveatus Mocsáry 1914: 1. Lectotype ♂ (designated by Móczár 1964: 445); Bosnia (MNSB) (examined). Elampus sanzii [nec Gogorza, 1887]: Dyntaxa 2013. Material examined. * Estonia: Tartu, 16.VI.2013, 1 ♀ (T. Tammaru). * Finland: Ab : Turku, 25.VII.1967, 1 ♀ (E. Valkeila); N : Helsinge, Malm [= Helsinki Malmi], 4.VII.1920, 1 ♀ and 7.VI.1921, 3 ♀♀ (R. Forsius); Helsinki, Viikki, 2.VI.2008, 1 ♀ (J. Paukkunen); Sa : Mikkeli, 16.VII.1941, 1 ♀ (V.J. Karvonen); Ta : Hattula, Parola, 4.VII.1974, 1 ♀ (J. Kangas); Hämeenlinna, 7.VII.1974, 1 ♀ (E. Valkeila); Janakkala, Kalpalinna, 16.VII.2008, 1 ♀ (V. Vikberg). * Norway: BØ : Kongsberg, Laugerudmoen, 11.VI–12.VII.2012, 1 ♀ (F. Ødegaard); HES : Kongsvinger, Granli, 6.VI.2011, 2 ♀♀ (F. Ødegaard); ON : Dovre, Hjelle, 10.VI.2012, 1 ♀ (F. Ødegaard). * Sweden: Ha [= Halland], 1883, 1 ♀ (A.S. Mortonsson); Sk : Höör, VI.1902, 1 ♂ (H. Rosén); Kristianstad, Vinslöv, sandy railroad verge, 12.V–16.VI.2008, yellow pan trap, 1 ♀ (M. Franzén); Sm : Värnamo, Rydaholm, sandy railroad verge, 17.VI–9.VII.2008, yellow-pan trap, 1 ♂ (C. Jonsson); Vb : Skellefteå, Finnforsfallet, 7.VII.2012, 1 ♀ (S. Hellqvist); Umeå "Bussjöbanan", gravel pit, 28.VI.2010, 1 ♀, and 2.VII.2010, 1 ♀ (S. Hellqvist). Distribution. * Estonia, * Finland, * Norway, * Sweden.—Transpalearctic: from Netherlands to Siberia (UsolyeSibirskoye). The general distribution is still poorly known, because many authors have confused E. foveatus with other closely related taxa. Remarks. The species has been recently found from museum collections in Estonia, Finland, Norway and Sweden. Earlier it had been mixed with other species of Elampus . It is new to the Nordic and Baltic countries. Surprisingly, all but two specimens recorded so far have been females, although males are usually more commonly collected in Elampus . : Published as part of Paukkunen, Juho, Rosa, Paolo, Soon, Villu, Johansson, Niklas & Ødegaard, Frode, 2014, Faunistic review of the cuckoo wasps of Fennoscandia, Denmark and the Baltic countries (Hymenoptera: Chrysididae), pp. 1-67 in Zootaxa 3864 (1) on pages 14-15, DOI: 10.11646/zootaxa.3864.1.1, http://zenodo.org/record/4930433 : {"references": ["Mocsary, A. (1914) Chrysididae plerumque exoticae novae. Annales Musei Nationalis Hungarici, 12, 1 - 74.", "Gogorza, J. (1887) Crisididos de los alrededores de Madrid. Anales de la Sociedad Espanola de Historia Natural, 16, 17 - 88.", "Dyntaxa (2013) Svensk Taxonomisk Databas - Swedish Taxonomic Database (version 1.1.5059.20729). Available from: http: / / www. dyntaxa. se / (accessed 1 November 2013)"]}